Tingkat pengetahuan, persepsi, dan sikap konsumen terhadap kehalalan obat di Apotek UNISIA 24 Taman Sari Yogyakarta - Sahlia, Siti Afifah; A Hi Wahid, Rahmat (University Of Darussalam Gontor, 2025)
Indonesia is one of the countries with the largest Muslim population in the world. So that public awareness and knowledge related to halal product guarantees is very important, one of which is the guarantee on pharmaceutical products. The purpose of this study was to determine the high level of knowledge, perceptions, and attitudes of consumers at the UNISIA 24 Taman Sari Yogyakarta Pharmacy. The research was conducted from March to May 2023. This research is a descriptive observational type. The data collection instrument uses a questionnaire and the data results are processed using statistical analysis applications. The results showed, at the level of knowledge it was known that 53% were categorized as good, 45% were categorized as sufficient and 2% were categorized as deficient. In perception, it is known that 92% are categorized as good and 9% are categorized as sufficient, in attitude it is known that 87% of respondents are categorized as good and 13% are categorized as sufficient. Based on this, it can be concluded that the average value of the level of knowledge (77%), perception (83%) and consumer attitudes (84%) towards the halalness of drugs at the UNISIA 24 Taman Sari Yogyakarta Pharmacy is in the good category.